Management of Filial School Development (Case Study on Management Standards on Singkawang 11 State Junior High School) - Yusak Ujang; M Syukri; Sukmawati Sukmawati (JETL (Journal of Education, Teaching and Learning), 2018)
The filial school is one of the model of school development where learners study and learn various skills as the basic capital to continue to higher education level. The responsibility of the school's management is fully filial by the parent school in accordance with the quality standards of education services. This research aims to reveal the management of philial school development on the standard of management at Singkawang 11 State Junior High School (SMP Negeri 11 Singkawang ) with the focus of: 1) development planning of filial school in management standard, 2) organizing the development of filial school in management standard, 3) implementation of filial school development on management standard, 4) supervision of filial school development on management standards, 5) constraints faced in the development of filial schools on management standards, and 6) efforts undertaken in the development of filial schools on management standards. The research method used descriptive research with qualitative approach. Data collected by in-depth interviews, participant observation, documentation and analyzed by data reduction, data presentation, conclusion or verification. Testing of data reliability is done by extending the observation period, and triangulation and member checking. The results of the study conclude: 1) Filial School Development Planning in Management Standards, has been done by Singkawang 11 State Junior High School  by making the vision and mission is implied that support the implementation of philial school development and has been socialized and arranged based on consultation with certain teachers by considering the needs of the school as a basis making, 2) organizing the development of filial schools on the standard of management, that the head of Singkawang 11 State Junior High School  has arranged the organizational structure in connection with the division of main tasks and functions of the teacher and socialized. 3) Implementing the development of filial schools on the standard of management that Singkawang 11 State Junior High School  refers to document I which includes all aspects of school management including philial schools covering curriculum aspects, student aspects, educator aspect and educational staff, aspects of facilities and infrastructure, finance and financing , school culture and school areas, school committees and partnerships, and school management information systems, 4) supervision of filial school development on process standards, that Singkawang 11 State Junior High School  has conducted School Self Evaluation (EDS) conducted annually as a basis for preparation of the Plan School Work (RKS) and principals have conducted classroom supervision activities on teachers. For managerial supervision of the eight national standards of education by school supervisors has been undertaken but not scheduled, 5) The barriers faced in the development of filial schools in management standards consist of internal (internal) and external (external) barriers. obstacles from within include the limitations of learning facilities and infrastructure of students in the form of limited learning buildings, laboratories, libraries, canteen, prayer room, learning books and desks and student learning seats. External obstacles in the form of poor, perforated, and muddy access roads make it difficult for teachers to carry out teaching duties at the filial schools. 6) The efforts made in the development of filial schools in the management standards include the proposal for the rehabilitation of the 2017 study by the principal to the education and cultural offices of Singkawang city, the cooperation of the principal of Singkawang 11 State Junior High School with Singkawang 3 State Junior High School in a grant program of learning facilities in the form of help desk and desk study as well as reference books for studying students in filial schools.